The Role of Indian Entrepreneurship Ecosystem in the Era of Climate Change - Agarwal, Richa; Pundir, Swati; Pokhriyal, Ashok Kumar (AMC Indian Journal of Entrepreneurship, 2022)
Entrepreneurship depends on an environment that fosters new ideas. Previous research on the entrepreneurship ecosystem has enhanced the origin of entrepreneurship and made entrepreneurs interact with external business environments. Hence, this conceptual framework aimed at connecting the entrepreneurship ecosystem with the five big dimensions of biological concepts which reflected on how entrepreneurship is responsible for climate change. It also discussed the general outlines of Entrepreneurial Ecology theory. The researcher used biological analysis to investigate the characteristics of entrepreneurial activity, and it led to ecological analysis. The study also went through other analysis to describe concepts more deeply. It suggested that the government should promote the education of the entrepreneurship ecosystem in higher educational institutions and universities and include traditional knowledge in the context of biodiversity and ecology. It would help human interactions with the natural environment and secure inter-generational equity